Modulation of multidrug resistance protein expression in porcine brain capillary endothelial cells in vitro - Gutmann, Heike; Török, Michael; Fricker, Gert; Huwyler, Jörg; Beglinger, Christoph; Drewe, Jürgen (Drug metabolism and disposition, 1999)
Multidrug resistance-associated protein (MRP) is a transport system that is involved in the elimination of xenobiotics and biologically active endogenous substrates. Recently, the presence of MRP has been demonstrated in cultured brain capillary endothelial cells (BCECs). The time-dependent, functional expression of MRP in porcine BCECs was investigated to assess the value of this cell culture model for drug transport at the blood-brain barrier. Western blot analysis was used to investigate MRP expression in freshly isolated porcine BCECs and compared to MRP expression at days 8 and 10 in culture. Subcellular localization of MRP was investigated by immunocytochemistry with an MRP-specific monoclonal antibody, MRPr1. Functional activity of MRP was assessed by efflux studies with the fluorescent MRP substrate glutathione-methylfluorescein (GS-MF). No significant MRP expression was detected in freshly isolated endothelial cells. However, MRP expression is up-regulated in cell culture in a time-dependent manner. Immunostaining revealed predominantly perinuclear and, to a lesser degree, plasma membrane localization of MRP. At 10°C GS-MF efflux was significantly decreased, indicating the involvement of an energy-dependent transport system. Efflux of GS-MF was apparently inhibited by MK571, a specific inhibitor for MRP. Porcine BCECs demonstrate up-regulation of functional MRP expression during culture, as observed in human tissue, and therefore might serve as a useful in vitro system for studying MRP-mediated blood-brain barrier transport.
Gesehen am 26.04.2017